(untitled) (Economic and Political Thought, 2017)
The subject of this article is the problem of institutional transformation, specifically its economic aspects, in countries of the former USSR. First, selected theoretical aspects related to institutional transformation of post-communist economies are discussed. Then, a synthetic analysis of the advancement of this transformation in the post-Soviet area and of its consequences for the development and international competitiveness of their economies is conducted. And finally, reference is made to the future of institutional transformation of post-Soviet economies. The analysis shows that: from the very beginning (i.e. the break-up of the USSR), the processes of institutional transformation of post-Soviet economies have been strongly differentiated both in terms of adopted transformational strategies and their effectiveness, as evidenced by the very different results observed presently in this regard; the current level of development, as well as international competitiveness of most post-Soviet economies are not a direct consequence of the advancement of their institutional transformation; completion of the processes of institutional transformation is not to be expected in the foreseeable future and neither is the introduction of a liberal institutional environment typical for free market economies.